Renal biopsy in children with nephrotic syndrome: a study of histopathological pattern - Joshi, Trupti A.; Joshi, Amol K. (International Journal of Contemporary Pediatrics, 2019)
Background: Idiopathic nephrotic syndrome (INS) is a common childhood renal disease characterized by a remitting and relapsing course, associated with different histopathological subtypes. The true incidence of various histopathological subtypes of NS remains under estimated owing to the diversity in indication criteria for performing renal biopsies in pediatric population. Methods: This was a cross-sectional observational study in children with nephrotic syndrome at a tertiary health care centre. Total 22 children, with nephrotic syndrome, who underwent renal biopsy procedure during a period of one year, were enrolled for the study. Indications of renal biopsy were noted, and the histopathology reports were studied in detail. Results: In this study group, the most common indication for renal biopsy was “Atypical age (> 8years) of diagnosis in 45.5% (10/22) patients, followed by 22.7% (5/22) in “Children presenting with hypertension and hematuria”. The most common histopathological finding in these children was mesangial proliferative glomerulonephritis in 45.5% (10/22) patients followed by IgA nephropathy with mesangial proliferation in 22.72% (5/22) and minimal change disease in only 13.6% (3/22). Conclusions: This study highlights the occurrence of non-MCD as the common cause of INS in the children and denotes the significance of performing renal biopsies in children with INS for better prognostication.